2021
DOI: 10.1007/s10067-021-05675-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SARS-CoV-2 coronavirus infection in patients with systemic lupus erythematosus from a single center in Catalonia

Abstract: Objective To evaluate the incidence and characteristics of SARS-CoV-2 infection among patients with systemic lupus erythematosus (SLE) and to compare it to that described in the general population. Methods For 5 weeks, we carried out a cross-sectional study consisting of telephone interviews of SLE patients. We collected epidemiological data, symptoms suggesting COVID-19, results of nasopharyngeal swabs, and ongoing treatments. In those patients who required hospital ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
3
12
1
Order By: Relevance
“…Although varying incidence rates have been observed, most studies reported similar or lower incidences for COVID-19 in patients compared with controls. 21–23 These findings correspond with our own results, and are in line with our earlier observation that patients are less likely to be exposed to SARS-CoV-2 compared with the general population due to stricter adherence to social distancing measures. 24 Results of studies investigating the risk of patients with rheumatic diseases to develop severe COVID-19 manifestations, such as hospital/ICU admission or death, have been contradictory as well.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although varying incidence rates have been observed, most studies reported similar or lower incidences for COVID-19 in patients compared with controls. 21–23 These findings correspond with our own results, and are in line with our earlier observation that patients are less likely to be exposed to SARS-CoV-2 compared with the general population due to stricter adherence to social distancing measures. 24 Results of studies investigating the risk of patients with rheumatic diseases to develop severe COVID-19 manifestations, such as hospital/ICU admission or death, have been contradictory as well.…”
Section: Discussionsupporting
confidence: 93%
“…Since the start of the COVID-19 pandemic, numerous studies on the incidence and severity of COVID-19 in patients with rheumatic autoimmune disease have been published. Although varying incidence rates have been observed, most studies reported similar or lower incidences for COVID-19 in patients compared with controls 21–23. These findings correspond with our own results, and are in line with our earlier observation that patients are less likely to be exposed to SARS-CoV-2 compared with the general population due to stricter adherence to social distancing measures 24.…”
Section: Discussionsupporting
confidence: 91%
“…There was only one SLE patient who was admitted with COVID-19, and she was discharged well. This concurred with the study by Espinosa G et al [ 3 ] which showed that the incidence of COVID-19 is low in a cohort of SLE patients with stable and clinical inactive disease and all SLE patients with confirmed SARS-CoV-2 infection in their study recovered.…”
supporting
confidence: 91%
“…The study was limited by the self-reporting nature of participating nephrologists but demonstrated that those impacted with SARS-CoV2 had similar reassuring rates of hospitalization, need for respiratory support, and mortality as children not treated with chronic immunosuppression [ 53 ]. Surveys have been done of adult patients with SLE that suggest similar infection rates and severity levels as those without SLE, but as yet there are no pediatric reports [ 54 ]. All of these studies are limited by enrollment bias, reporter bias, and the cross-sectional nature of the reports, not to mention that they are reports from the earlier waves which do not include newer virus variants that seem to have disproportionate effects in children.…”
Section: Sars-cov2 Infection In Special Pediatric Nephrology Populationsmentioning
confidence: 99%